(untitled) (مجلة المنصور, 2022)
The research aims to deepen understanding of the issue of quality cost and the dimensions of the quality of health service in the medical fields, and determine the relationship between quality costs and the dimensions of the quality of health service, and the impact of the quality costs of the dimensions of the quality of health service, and adopted the research methodology and descriptive (exploratory and analytical), through a questionnaire included (50) items, and select Find a set of hypotheses that have been tested statistical tools, and was selected a random sample of (50) members of the Baghdad Teaching Hospital out of the community’s (127) individual, as was the proportion of respondents (76%). The research found a set of conclusions, the most important is that the angel of the hospital research sample weak interest in monitoring the quality of health services provided to the patient, this means that problems occur in patients during their access to treatment, and lack of seeking medical personnel at the hospital to provide health services needed by the patient quickly and promptly and hence the low level of the dimensions of the quality of health service and the high quality of health services provided cost rates.